Hungarian Refugees' Hunger Strike - Héderváry, Claire de (1957)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Hungarian refugees in Austria continue their hunger strike against the American decision. Reuters report.